“Politics is not a Spectator Sport”: Proverbs in the Personal and Political Writings of Hillary Rodham Clinton - Mieder, Wolfgang (Tautosakos darbai, 2015)
Hillary Rodham Clinton is a thoughtful proverbial stylist in her books It Takes a Village and Other Lessons Children Teach Us (1996), Living History (2003), and Hard Choices (2014). Just as other politicians, she too has attempted to formulate concise statements that have the possibility of becoming familiar quotations and perhaps even proverbs. Being a world traveler she has picked up foreign proverbs which she incorporates into her communications with appropriate introductory formulas. But she also draws special attention to English language proverbs, changing some of them to expressive anti-proverbs. She appreciates the fact that the complex interplay of proverbs and political language is of great importance as she writes to communicate her thoughts on American political history and the future role that the United States might play in the world. In doing so, she does not employ proverbs as an ideological instrument but rather as a linguistic tool to enhance her often quite factual prose with vivid metaphors. Looking at her instantiation of proverbs shows the fundamental polysituativity, polyfunctionality, and polysemanticity of proverbs in actual contexts. Each proverb occurrence offers new insights into her being, her reflections, and her aspirations for herself and for her country. Whatever one might think of her political agenda, she most certainly has proven herself to be an engaged and experienced leader in the United States and on the world stage.